The challenges of women in leadership positions: a case Study of Sekyere Rural Bank Limited. - Ampiah, Esi Patricia (KNUST, 2025)
A Thesis Submitted To The Department Of Human Resource And Organisational Development In Partial Fulfilment Of The Requirements For The Degree Of Master Of Business Administration (HRM Option).